2009
DOI: 10.1016/j.jacc.2008.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Coronary Stent Thrombosis

Abstract: Important correlates of ST were identified. Discontinuation of clopidogrel, undersizing of the coronary stent, present malignancy, and intermediate (>or=50% to <70% stenosis) coronary artery disease proximal to the culprit lesion were the strongest predictors of ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(142 citation statements)
references
References 20 publications
4
130
2
6
Order By: Relevance
“…When a stenting strategy is applied, selection of the appropriate stent diameter may be of particular importance during PPCI, since stent undersizing is one of the most powerful predictor of ST among non-elective PCI [92] . Actually, the reference vessel diameter of the IRA may be difficult to accurately assess during PPCI, because of thrombus burden, cathecholamine stimulation and inflammatory substances, that can contribute to general and localized vasocostriction [93] .…”
Section: Embolic Protection Devicesmentioning
confidence: 99%
“…When a stenting strategy is applied, selection of the appropriate stent diameter may be of particular importance during PPCI, since stent undersizing is one of the most powerful predictor of ST among non-elective PCI [92] . Actually, the reference vessel diameter of the IRA may be difficult to accurately assess during PPCI, because of thrombus burden, cathecholamine stimulation and inflammatory substances, that can contribute to general and localized vasocostriction [93] .…”
Section: Embolic Protection Devicesmentioning
confidence: 99%
“…Additionally, it is of paramount importance to achieve the largest possible lumen cross-sectional area. Many studies (with both metal stents and scaffolds) identify a small final lumen cross-sectional area as a predictor of ST. 67 The Virchow triad for thrombogenesis can be almost completely controlled by the operator. 65 The doctor can optimize: (1) the lumen with appropriate pre-and postdilation; and (2) the flow by selecting the appropriate vessel (with adequate size, run-off, without myocardial bridging and supplying viable myocardium).…”
Section: Current Status Between Promises and Pitfalls Of Bvsmentioning
confidence: 99%
“…Currently, the prevalence of AST varies between 0.1 and 1.7% [1,2,3,15]. Cumulative incidence of AST was 0.6% (140 out of 21,009 patients) [19] and 0.1% (24 out of 23,500 patients) [20] based on 2 large-scale and multicenter registry studies. European Ambulance Acute Coronary Syndrome Angiography (EUROMAX) trial indicated that the risk period for AST was limited to the first few hours (median time to AST was 2.3 h, interquartile range 1.9-2.8 h) after PCI [1].…”
Section: Epidemiologymentioning
confidence: 99%